If X = 6a + 86 + 9c ; Y = 2b – 3a – 6c and Z = C – B + 3a ; Find : (I) X + Y + Z (Ii) X – Y + Z (Iii) 2x – Y – 3z (Iv) 3y – 2z – 5x - Mathematics

Advertisement Remove all ads
Sum

If x = 6a + 86 + 9c ; y = 2b – 3a – 6c and z = c – b + 3a ; find :
(i) x + y + z
(ii) x – y + z
(iii) 2x – y – 3z
(iv) 3y – 2z – 5x

Advertisement Remove all ads

Solution

(i)                     x =     6a + 8b + 9c
                         y = − 3a + 2b − 6c
                         z =  +3a  −  b +   c     
Adding x + y + z =    6a  + 9b + 4c    

 (ii) x − y + z = (6a + 8b + 9c) − (2b − 3a − 6c) + (c − b + 3a)

= 6a + 8b + 9c − 2b + 3a + 6c + c − b + 3a

= 6a + 3a + 3a + 8b − 2b − b + 9c + 6c + c

= 12a + 5b + 16c

(iii) 2x − y − 3z = 2(6a + 8b + 9c) − (2b − 3a − 6c) − 3(c −b + 3a)

= 12a + 16b + 18c − 2b + 3a + 6c − 3c +3b − 9a

= 12a + 3a − 9a + 16b + 3b − 2b + 18c + 6c −3c 

= 6a + 17b + 21c

(iv) 3y − 2z − 5x = 3(2b − 3a − 6c) − 2(c − b + 3a) − 5(6a + 8b + 9c)

= 6b − 9a − 18c − 2c + 2b − 6a − 30a − 40b − 45c

= − 9a − 6a − 30a + 6b + 2b − 40b − 18c − 2c − 45c

= − 45a − 32b − 65c

Concept: Combining like Terms
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 11 Algebraic Expressions
Exercise 11 (B) | Q 9 | Page 140
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×